2018
DOI: 10.1097/jom.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factors in Québec Male Firefighters

Abstract: A high proportion of Québec firefighters are at moderate to high risk of CVD. These findings suggest that Québec fire departments should help all firefighters to adopt and maintain a healthy lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
2
16
2
1
Order By: Relevance
“…By contrast, the overall frequency of overweight plus obese firefighters in our study was quite high (59.64%). This finding is similar to what has been described for other populations of firefighters within and outside of Brazil15 16 31 34 36 39 and surpasses the prevalence observed among the Brazilian adult man (BMI ≥25 kg/m 2 ; 57.6%) 4. There are two possible explanations for these apparently conflicting results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…By contrast, the overall frequency of overweight plus obese firefighters in our study was quite high (59.64%). This finding is similar to what has been described for other populations of firefighters within and outside of Brazil15 16 31 34 36 39 and surpasses the prevalence observed among the Brazilian adult man (BMI ≥25 kg/m 2 ; 57.6%) 4. There are two possible explanations for these apparently conflicting results.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of obese firefighters (BMI ≥30 kg/m 2 ) in our study was lower (10.99%) compared with the prevalence reported in the Brazilian population of adult males (18.5%) 4. Our study also showed a lower obesity prevalence when compared with firefighter populations of the USA9 31–35 and Canada 36. On the other hand, two studies that described obesity (using BMI) among Brazilian firefighters from the Federal District showed similar frequencies of obese firefighters compared with our study 15 16.…”
Section: Discussionsupporting
confidence: 73%
“…In female firefighters, age was a significant predictor of BMI and WC, and age, BMI and WC were significant predictors of DBP. Philippe Gendron et al (2018a) reported that, in male firefighters, BMI was significantly different between the group that presented with no CAD risk factors compared to the group with one or more risk factors. Choi et al (2016c) reported that in both male and female firefighters, age was significantly correlated with BMI and WC in firefighters.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Liao et al [25] explored the correlation between firefighter injury frequency and duration, demographics, personality and economics, and they found that female firefighters reported 33% more injuries than their male counterparts. According to the 2013 ACSM guidelines, studies of Gendron et al [26,27] showed that 11% of female and 34.5% of male firefighters were categorized as having moderate cardiovascular disease (CVD) risk, while 65% of female and 43.6% of male as high CVD risk.…”
Section: Introductionmentioning
confidence: 99%